"Comarca de guitarras" y "Poetas nochernícolas". Musical style and symbolic borders around the Pampean folk music. (Revista Argentina de Musicología, 2018)
The title of this work refers to two musical compositions by "Cacho" Arenas. based on poems by Edgar Morisoli and Juan Carlos Bustriazo Ortiz respectively. Guitars and poets represent two significant elements to the constitution of the idea of a 'Pampean folk music'. We attempt to offer an approximation to the analysis of some musical elements and discursive strategies elaborated by a group of Pampean musicians to define a musical production called ·folklore· or 'música pampeana·. As an urban recreation of traditional practice. this music emerges as a sound model of demarcation of the local, within both the regional and national context. In this way. clearly defined borders arise from a particular way of 'making music'. in which the notions of "inspiration", "originality", "sensibility", "commitment", "testimony". include an ethical as well as a stylistic dimension. as opposed to a different 'music making', associated with massive consumption.
Keywords: Pampean folk music; genre; style; discoursive strategies